A Context-Based Approach To ProverbTranslation: The Case Of Chinese IntoPersian And Persian Into ChineseTranslation (Journal of Namibian Studies : History Politics Culture, 2024)
Translators and language learners often focus on finding direct equivalents of proverbs in the target language(TL), without considering context and linguistic structure. This paper proposes a context-based approach to proverb translation between Chinese and Persian languages, taking into account the proverb's contextual meaning, and linguistic form with context-based equivalences. The study suggests that, despite linguistic and cultural differences, there are ways to reduce cultural shock and linguistic bias meanwhile improving translation results and communication. In this study, we have employed a way to divide proverbs into three categories basic correspondence, semi-correspondence, and non- correspondence proverbs in both languages to facilitate the translation results.